Regularização fundiária urbana no município de Soledade: análise da política pública de regularização fundiária e acesso à moradia - Rosado, Lisiane Forti (2018)
This study aims to describe the urban land regularization program in the municipality of Soledade, with the subsequent analysis of public housing policies and access to housing. Initially, land regularization planning was carried out together with Soledade, starting from the legal-legislative analysis of the land demands in the urban scenario and passing to the analysis of the documents that describe the project. Urban planning and its characteristics along the municipal urbanization scenario are another point that complement the present study, hence the urban concentration occurred in a disorderly way, due to the lack of adequate planning of the cities. In addition, the lack of adequate housing, which includes water supply, sanitation, legal security of tenure and access to electricity, among other public services, bring problems in the social and economic sphere. The fundamental and social right to housing to be implemented requires housing policies, which are based on the City Statute. One obstacle to be solved by the actors of law in postmodernity is to face the difficulties imposed by housing policies, since there is a lack of measures to realize the right to housing for all. For this right to be observed, it is necessary to overcome the shortcomings arising from the lack of public housing policies. Given this, the judicialization has been pointed out as an alternative to the problem of the lack of decent housing for the population. In this study, it was possible to conclude that effective government actions are necessary, that strengthen democracy and implement the access to decent housing for families. The judiciary, in turn, in its primary role of control, must be an ally in the implementation of public policies in the face of the real needs of citizens.